Germ cell mosaicism for AUTS2 exon 6 deletion - Gieldon, Laura; Jauch, Anna; Obeid, Katharina; Kaufmann, Lilian; Hinderhofer, Katrin; Haug, Ulrich; Moog, Ute (American journal of medical genetics, 2021)
Haploinsufficiency of AUTS2 has been associated with neurodevelopmental disorders and dysmorphic features (MIM # 615834). More than 50 patients have been described, mostly carrying de novo deletions of one or more exons, including eight patients with exon 6 deletions. We report on two siblings, a girl and a boy aged 11 and 13 years, in whom the same pathogenic 85 kb deletion on 7q11.22 encompassing exon 6 of AUTS2 by SNP array analysis was identified. Both children had typical symptoms of AUTS2 syndrome such as intellectual impairment and behavioral problems, but with markedly different expression. SNP array analysis excluded the deletion in blood samples of both parents and a healthy brother. Conventional karyotyping of both parents and additional FISH analyses, marking the flanking regions of the deletion, did not show any structural rearrangements involving 7q11.22. A germ cell mosaicism was suggested as the most probable explanation for occurrence of the same deletion in these two siblings. To our knowledge this is the first report of germ cell mosaicism for AUTS2 syndrome. It additionally provides further evidence of intrafamilial phenotypic variability in AUTS2 syndrome and adds clinical information to the phenotypic spectrum of patients with AUTS2 exon 6 deletions.
Gesehen am 28.11.2022